Fatal graft-versus-host disease after allogeneic stem cell transplantation in a patient recently exposed to nivolumab. (March 2019) - Jiménez-Ubieto, Ana; Rodriguez, Antonia; Martinez Sánchez, Pilar; Gómez, Adolfo; Rodriguez, Yolanda; Carreño-Tarragona, Gonzalo; Martinez-López, Joaquín; Grande, Carlos
Allogeneic hematopoietic stem cell transplantation and checkpoint blockade therapy are immune-based salvage therapies for Hodgkin's lymphoma; however, the use of programmed death 1 blocking agents in the allogeneic stem cell transplantation setting could augment the incidence of steroid refractory graft-versus-host disease. Few studies suggest that that nivolumab is safe in patients previously treated with an allogeneic stem cell transplantation. Likewise, there are very limited data on the use of nivolumab before allogeneic stem cell transplantation. Here, we report a case of fatal graft-versus-host disease in a patient who underwent allogeneic stem cell transplantation 26 days after the last administration of nivolumab. Careful monitoring and close clinical assessment of atypical presentation for graft-versus-host disease in these patients, interval of time from nivolumab administration to allogeneic stem cell transplantation, drug dosage adjustments or more effective allo prophilaxys should been evaluated in prospective clinical trial.